Guillain–Barré Syndrome Secondary to West Nile Virus in New York City - Rafail Beshai; Daniel Bibawy; Joseph Bibawy (Case Reports in Infectious Diseases)
West Nile virus (WNV) is an arthropod-borne flavivirus belonging taxonomically to the Japanese encephalitis subgroup. Usually, it is transmitted by Culex pipiens mosquitoes. Consequently, an increase in WNV-positive mosquitoes presents a rise of the number of patients, as it has been seen in NYC. We present a 65-year-old patient with WNV infection who presented with Guillain–Barré syndrome (GBS). She had a rapidly progressing ascending paralysis, a common feature in GBS patients but an uncommon presentation in WNV. Realizing WNV as an emerging pathogen along with its uncommon presentation of GBS can be potentially lifesaving if caught at an early stage.